Youth motor competence across stages of maturity: Perceptions of physical education teachers and strength and conditioning coaches - Burton, A. M.; Eisenmann, J. C.; Cowborn, I.; Lloyd, R. S.; Till, K. (PLOS ONE, 2022)
Physical education (PE) teachers and strength and conditioning (S&C) coaches are well placed to develop motor competence within youth populations. However, both groups` perceptions of important motor competencies are relatively unknown, especially when considering stage of maturity. Therefore, this study aimed to 1) present PE teachers and S&C coaches` perceptions of motor competence importance according to stage of maturity; 2) compare perceptions of motor competence between stages of maturity, and between PE teachers and S&C coaches; and 3) explore factors that influence PE teachers and S&C coaches` perceptions of motor competence importance. Via a mixed-method questionnaire, 47 PE teachers (professional experience = 10.3±6.6 years) and 48 S&C coaches (professional experience = 8.6±4.8 years) rated the importance of developing 21 motor competencies across four stages of maturity (childhood, pre-peak height velocity [PHV], circa-PHV, and post-PHV) using a Likert-scale (1 = not important, 5 = very important). Participants also provided open-ended explanations for their perceptions. Frequency analysis indicated that participants rated a broad range of competencies important, with S&C coaches rating more competencies important than PE teachers across all stages of maturity. Mixed-model analysis highlighted several differences in motor competence importance when comparing perceptions between participant groups, and between stages of maturity for PE teachers and S&C coaches. For example, S&C coaches rated strength-based motor competencies less important during childhood (d = -1.83 to -0.43), while PE teachers rated them less important during childhood (d = -2.22 to -0.42) and pre-PHV (d = -1.70 to -0.51) compared to other stages of maturity. Codebook thematic analysis showed several factors that influenced participant`s perceptions of motor competence importance (e.g., participants understanding of themselves). The findings suggest that multiple environments may be required to adequately facilitate motor competence development amongst youth. Coach education should target misunderstandings around the risks of strength-based activity during early stages of maturity and the benefits of developing strength-based motor competencies across youth populations.